Pengaruh Persepsi Resiko, Kemudahan, Kegunaan , dan Kepercayaan Terhadap Sikap Dalam Penggunaan Mobile Banking (Survey pada nasabah Bank BRI, Bank Mandiri , dan Bank BNI di Solo) - Atika Safitri, Widya, Dr. Erma Setiawati, MM.,CA (2016)
This study purposes to examine and analyze factors - factors that influence attitudes in the use of mobile banking by modifying the model of the Technology Acceptance Model (TAM) developed by Davis on tahun1989. The population used in this study are customers of Bank Mandiri, Bank BRI and Bank BNI in solo. Data collection was performed using a questionnaire. The sampling method using convinience sampling method. The total samples collected as many as 90 customers. Analysis technique used is multiple linear regression. The results of the analysis for this model indicate that the construct is the perceived Ease of use, perceived usefulnes and trust affect the attitudes in the use of mobile banking, otherwise the perceived risk does not affect the attitude in the use of mobile banking. This means that the attitude in the use of mobile banking is influenced by the perceived Ease of use, perceived usefulness, and trust. Keywords: Technology Acceptance Model (TAM), perceived risk, perceived Ease of use, Perceived Usef ulness, Trust, attitudes in the use of mobile banking